A Peep into the Society through a Kitchen - Niva Jacob; Sashi B Gupta; Suganya PPK Pillai; Chandrashekar M; Preeti S (Indian Journal of Private Psychiatry)
Most females in our society are having a difficult married life but not many of them are having the privilege or courage to walk out of it or stand up for their rights, as they are uneducated or helpless due to financial dependence or even the societal pressure. After a period of sustained silence, they might end up having depression or other mental health issues or even end their lives. Some believe it is the right thing to do and enjoy it by blindly following it. Some suppress their emotions and dreams and passively live their life and go unrecognized. Some stand up for their rights and might even break their marriages. Some lucky females get to be married as well as live a life without such issues due to progressively thinking husbands and families where marriage is considered a partnership instead of ownership, where both partners accept egalitarian roles. The patriarchal ideas existing in the society and the magico-religious beliefs existing around menstruation are also addressed.